2019
DOI: 10.3390/catal9100808
|View full text |Cite
|
Sign up to set email alerts
|

Single-Atom X/g-C3N4(X = Au1, Pd1, and Ru1) Catalysts for Acetylene Hydrochlorination: A Density Functional Theory Study

Abstract: The mechanisms of the single-atom X/g-C3N4(X = Au1, Pd1, and Ru1) catalysts for the acetylene hydrochlorination reaction were systematically investigated using the density functional theory (DFT) B3LYP method. The density functional dispersion correction obtained by the DFT-D3 method was taken into account. During the reaction, C2H2 and HCl were well activated and the analysis of the adsorption energy demonstrated the adsorption performance of C2H2 is better than that of HCl. The catalytic mechanisms of the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…44 Thus, in order to simulate the maximum active space, we chose three adjacent tri- s -triazine units as the initial structure for the study and optimized it. 33 Hydrogen atoms saturated the dangling bonds of the boundary atoms to simplify the cluster model, thus the surface edges were not taken into account. By optimizing the cluster model, two configurations, namely corrugated and planar, were obtained, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…44 Thus, in order to simulate the maximum active space, we chose three adjacent tri- s -triazine units as the initial structure for the study and optimized it. 33 Hydrogen atoms saturated the dangling bonds of the boundary atoms to simplify the cluster model, thus the surface edges were not taken into account. By optimizing the cluster model, two configurations, namely corrugated and planar, were obtained, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Then, the obtained supercell was imported into GaussView software, and the redundant atoms were deleted to obtain three adjacent tri-s-triazine units, in which the six N atoms at the boundary have hanging bonds, saturated with H atoms, according to a model that has been reported in other articles. 33,34 The atomic coordinates for the calculated structure of the g-C 3 N 4 cluster are shown in Table S1 (ESI †). Moreover, the lowest energy structure for g-C 3 N 4 was a structure with M = 1 spin multiplicity.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Our group has conducted extensive study on micelle catalysis, different organocatalyst [29][30][31] and organometallic catalyst [32,33] Grubbs catalyst was synthesized according to the previously reported method [34]. Exo-5-norbornene-2-carboxylic acid was synthesized according to our previous report [35].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they demonstrated that pyridinic N and pyrrolic N maybe the active sites for hydrogen chloride and acetylene, and pore character effect on catalysis by experiment and DFT. 17,19,20,[22][23][24][25] Li and coworkers also reported many works of mercury-free catalyst, including nitrogen-doped carbon catalyst for acetylene hydrochlorination. 26 Jiang and co-workers reported the catalytic coupling reaction of acetylene and ethylene dichloride to synthesize VCM using nitrogen-doped activated carbon (AC) as the catalyst.…”
Section: Introductionmentioning
confidence: 99%